(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Assessing knowledge and practice of breastfeeding among postpartum mothers and analyzing associated factors at Di Linh District Medical Center, Lam Dong province. Methods: This is a cross-sectional study with analysis of 380 postpartum mothers at the Department of Reproductive Health and Obstetrics Care, Di Linh District Medical Center, Lam Dong Province. Results: This study shows that the proportion of research subjects with correct general knowledge about breastfeeding reached 60.3%, and correct general practice only reached 47.9%. Conclusion: There is an association between correct knowledge about breastfeeding with age group, place of residence, gender, and there is an association between correct knowledge about breastfeeding and correct practice.